FEATURES OF NON-COMMON VOCABULARY OF ENGLISH LANGUAGE (Лучшие интеллектуальные исследования, 2025)
This thesis explores the features of non-common vocabulary in the English language, focusing on words and phrases that are less frequently used or unfamiliar to native speakers. By analyzing the linguistic characteristics and usage patterns of these words, the study aims to shed light on their significance in communication and language comprehension. Through a combination of theoretical analysis and empirical research, the thesis seeks to enhance our understanding of the diverse range of vocabulary in English and its impact on language proficiency. Ultimately, this research contributes to the broader field of linguistics by highlighting the importance of non-common vocabulary in shaping language diversity and complexity.